A content analysis study of scientific approach and authentic assessment in the textbook of Curriculum 2013 - Maryati Maryati; Enny Zubaidah; Ali Mustadi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This research aimed to describe the scientific approach and authentic assessment of the textbook based Curriculum 2013, on the theme “save living beings” for grade 6 students of elementary school such as textbooks published by Puskurbuk, Yudhistira, and Erlangga. The design of this study was content analysis. The instrument of the research was the analysis sheet based on theories. The validity of the instrument and the data was semantic validity and expert judgment. The reliability of the data was stability and reproducibility. The techniques of data analyzing consisted of unitizing, sampling, recording, reducing, inferring and narrating. The results of this study were; (1) The scientific approach contents consist of five aspects: observation, questions, trying, reasoning, and communicating, which are not in order. So not all indicators in every aspect of the scientific approach are found in each sub-theme. (2) Authentic assessment contents consist of three aspects: attitude assessment about social attitude and spiritual attitude, the psychomotor assessment contains only practice, product, and project assessment, and knowledge assessment without oral and assignment assessment.